The Ratio of Aspartate Aminotransferase to Alanine Aminotransferase (AST/ALT): the Correlation of Value with Underlying Severity of Alcoholic Liver Disease - Gurung, RB; Purbe, B; Gyawali, P; Risal, P (Kathmandu University Medical Journal, 2015)
Background Alcoholic liver disease is one of the most frequently diagnosed liver problems in the hospitalized patients in most tertiary care hospitals all over the world .The diagnosis of alcoholic liver disease is most of the time clinical. The AST/ALT ratio is a useful and reliable biochemical marker of liver injury due to alcohol. Whether the value of AST/ALT ratio correlates with clinical severity has not been studied. Objectives To study values of AST/ALT ratio in correlation with clinical severity of illness due to alcoholic liver disease using Child-Pugh’s grading. Methods This is a retrospective study. Inpatient records of all the patients admitted with diagnosis of alcoholic liver disease from July 2009 to 2011 June were analyzed. Data from 174 patients with the diagnosis of alcoholic liver disease - alcoholic hepatitis or alcoholic cirrhosis were retrieved; out of 174 patients, 138 were eligible for the study. The AST/ALT ratio and Child’s grading of all the patients were calculated from the documented biochemical and clinical parameters on admission. Demographic profile of all the patients were also recorded and analyzed. The data was analyzed using software SPPSS 16 version. Results A total of 138 patients diagnosed as alcoholic liver disease since July 2009 to June 2011 were analyzed. The male-female ratio was found to be 5.34: 1.The mean age of the patients at diagnosis was found to be 47.58 ± 12.83 years. Among 138 patients, Mongolian were found to have the highest prevalence of alcoholic liver disease (38.8%), followed by Newars ( 33.6%), Brahmin and Chhetri (19.1%) and Dalit (7.2%). With respect to AST/ALT ratio and Child’s grading of ALD, the mean AST/ALT ratio was found to be 3.03 ± 2.24 in those patients who had Chlild’s grade C; likewise the mean AST/ALT ratio was 2.28 ± 1.14, and 1.68 ± 0.83 in patients with Child B and Child A respectively. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12511 Kathmandu Univ Med J 2013; 43(3):233-236